Detecção molecular de Fusarium guttiforme, agente etiológico da fusariose do abacaxizeiro - Carnielli, Lorena (2014)
The pineapple crop has high significance in Brazil, due to its economic magnitude. However, diseases of the pineapple plant have caused major economic losses, and among those, the fusariosis is the most important. The etiological agent of the fusariosis is the fungus Fusarium guttiforme. The difficulty with the conventional diagnosis for correct identification has led to the search for new methods. In this study, the real time PCR method was tested with the goal of developing a rapid, specific and sensitive method for the diagnose of the F. guttiforme. The isolates were analyzed on its morphological characteristics and also identified by multiplex PCR (β-tubulin and factor 1-α gene) and by pathogenicity tests. In the diagnosis by real time PCR, SYBRGreen dye along with and a specific pair of primers for the elongation factor 1-α gene (tef1). The result obtained on the morphological characterization demonstrated that the micromorphological structures analyzed agreed with those described for the species and that there is variability in the growth of the isolates at 25ºC and 30ºC. In the pathogenicity test in seedlings of cv. Perola (susceptible) there was variation among isolates. The presence of two pairs of primers contributed to a low false number of negatives, but the test also had low specificity. However, the diagnostic by real time PCR showed good results, with high sensitivity (90,5%) and specificity (100%) with statistically significant p-value (p < 0,0001). The simplicity of the method, the specificity and the sensitivity using the SYBRGreen dye, indicates that de real time PCR technologies is recommended as fast, reduced risk of contamination and post-amplification detection of relatively low amount of target DNA. The ease of quantification and improving protocols makes real time PCR is a reference for the detection of Fusarium guttiforme in the pineapple plant.